BENTUK PENYAJIAN DAN SPESIFIKASI KESENIAN OGLEK TURONGGO SETO GEDANGAN, SENTOLO, SENTOLO KULON PROGO - Ambar Cahyani (Saraswati)
Oglek Sentolo art widely available in the Sentolo village, Kulon Progo regency. Almost in every pedukuhan (a little part of village, consist of aproximately 40 houses) in the Sentolo village have paguyuban (society) that engage in the field of oglek art. One is the paguyuban Turonggo Seto in Gedangan hamlet. Oglek art is an art form that belongs to the kuda kepang (horse braid) genre. Kuda kepang identical to a dance using kuda kepang property that tells the story of a riding soldier, with the trance scene on the crest of the show. Although it belongs to the genre of kuda kepang dance, oglek art has its own characteristics. Oglek art hallmark can be viewed and obtained from the elements in the form of performance such as the costumes worn, accompaniment, shape and motion properties and the order of performance.Based on the observation of Paguyuban Turonggo Seto oglek art forms can be seen the differences between oglek arts with the another kuda kepang art genre. The elements that exist in the performing arts of oglek Turonggo Seto can also be used as a differentiator between Oglek Turonggo oglek Seto with other arts that live in the same village, because the elements that exist in the oglek Turonggo Seto performance form has its own characteristics. These characteristics are only presented in the form oglek Turonggo Seto art performance so that people can easily recognize oglek art form the Paguyuban Turonggo Seto itself.Key words: Oglek Turonggo Seto, Spesifications